High-oil-seepage-resistance concrete applied to nuclear power engineering and preparation method of high-oil-seepage-resistance concrete
By regulating the ratio and process steps of raw materials in high-oil-resistant concrete, the problem of insufficient oil-porous-resistant performance of existing concrete is solved, and the effect of high-porous-resistant grade and low oil permeability is achieved, which meets the requirements of nuclear power engineering.
Patent Information
- Application Number
- CN202510068523.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When existing concrete faces mineral oil penetration, its oil seepage resistance is insufficient and cannot meet the requirements of nuclear power engineering for concrete oil leakage resistance.
High oil-resistant concrete consisting of silicate cement, fly ash, oil-proofing agent, mixed water, polycarboxylic acid high-performance water reducing agent, crude aggregate and machined sand is used to improve the mechanical properties and permeability of concrete by regulating the ratio of raw materials and process steps.
It has achieved high oil penetration resistance, with a level of 9-12 and an oil penetration rate of between 0.8-1.5%, meeting the needs of nuclear power engineering.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, and in particular to a high oil-permeability resistant concrete used in nuclear power engineering and a preparation method thereof. Background Art
[0002] During the use, repair and maintenance of mechanical equipment, mineral oil will penetrate and corrode concrete components, affecting the mechanical properties and service life of concrete components. Relevant studies have shown that compared with water, mineral oil has better wettability. As a hydraulic multiphase material, concrete produces and exists a large number of pores of different sizes, connected or non-connected, during the pouring, vibration, maintenance and hardening process. Therefore, mineral oil is more likely to penetrate and occupy the pores inside the concrete, thereby increasing the wedge-opening pressure of the pore wall, causing microcracks to spread over a large area, and ultimately reducing the compressive strength of the concrete.
[0003] The existing technology mainly improves the oil-proof performance of concrete by increasing the density of concrete and improving the pore structure of concrete. Specific measures include: 1) Rationally selecting cement types and strictly controlling cement dosage; 2) Optimizing aggregate grading and increasing the dosage of fine powder aggregate; 3) Using high-quality mineral admixtures, such as high-quality fly ash, silica fume, etc.; 4) Using high-quality and efficient water reducers and other admixtures; 5) Optimizing the pouring and vibration process; 6) Eliminating the pore channels caused by seepage through plastering, etc.
[0004] Although the above measures can effectively improve the oil permeability resistance of concrete, its oil permeability resistance is not high and cannot meet the requirements of the key casting parts of nuclear power projects for the oil permeability resistance of concrete. Therefore, developing a high oil permeability resistant concrete for nuclear power projects is of great significance to the field. Summary of the invention
[0005] To achieve the above object, the present invention provides a high oil-permeability resistant concrete for use in nuclear power engineering and a preparation method thereof.
[0006] The technical solution adopted by the present invention is:
[0007] A highly oil-resistant concrete for use in nuclear power projects, comprising the following raw materials by weight:
[0008] Portland cement 9-11%;
[0009] Fly ash 3.3-5.5%;
[0010] Oil repellent 1.25-2.5%;
[0011] Mixing water 6-8%;
[0012] Polycarboxylic acid high performance water reducing agent 0.18~0.22%;
[0013] Coarse aggregate 40~50%;
[0014] Artificial sand 30-35%.
[0015] Preferably, the highly oil-resistant concrete used in nuclear power projects is composed of the following raw materials by weight:
[0016] Ordinary Portland cement 10-10.6%;
[0017] Fly ash 4.3-5%;
[0018] Oil repellent 1.8-2%;
[0019] Mixing water 6.2-7%;
[0020] Polycarboxylic acid high performance water reducing agent 0.19~0.2%;
[0021] Coarse aggregate 41~45%;
[0022] The mechanical properties and impermeability of the concrete are the best when the artificial sand is 31-33%.
[0023] Preferably, the specific surface area of the ordinary Portland cement is 300-400m 2 / kg, density is 2.91-3.13kg / m 3 . Further improve the mechanical properties and impermeability of concrete.
[0024] Preferably, the water requirement ratio in the fly ash is 90-100%, which further improves the mechanical properties and impermeability of the concrete.
[0025] Preferably, the oil repellent comprises polyvinyl alcohol, nano-SiO2, FeCl3 and water, and the mass ratio of polyvinyl alcohol, nano-SiO2, FeCl3 and water is (48-59): (10-15): (30-37): 1. The mechanical properties and impermeability of concrete are further improved.
[0026] Preferably, the chloride ion content of the mixing water is ≤250 mg / L, the alkali content is ≤1500 mg / L, and the pH value is ≥5. This further improves the mechanical properties and impermeability of the concrete.
[0027] Preferably, the polycarboxylic acid high performance water reducing agent has a solid content of 18-22% and a water reduction rate of 25-35%, thereby further improving the mechanical properties and impermeability of concrete.
[0028] Preferably, the apparent density of the coarse aggregate is ≥2700 kg / m 3, crushing value ≤8%, mud content ≤0.2%. Further improve the mechanical properties and impermeability of concrete.
[0029] Preferably, the apparent density of the machine-made sand is ≥2600 kg / m 3 , mud content ≤ 0.2%. Further improve the mechanical properties and impermeability of concrete.
[0030] Any of the above methods for preparing highly oil-resistant concrete for use in nuclear power projects comprises the following steps connected in sequence:
[0031] (1) Prepare the raw materials according to the ratio, and divide the mixed water into three parts, which are used in steps (4-6) respectively;
[0032] (2) Pour the coarse aggregate and machine-made sand into the concrete mixing pot and stir for 30-60 seconds;
[0033] (3) Pour silicate cement and fly ash into the concrete mixing pot in sequence and stir for 30-60 seconds;
[0034] (4) Mix part of the mixing water and the polycarboxylic acid high-performance water reducer evenly, then pour into the concrete mixing pot and stir for 30-60 seconds;
[0035] (5) Mix part of the mixing water and the oil repellent agent evenly and pour into the concrete mixing pot and stir for 30-60 seconds;
[0036] (6) Use the remaining mixing water to clean the container containing the polycarboxylic acid high-performance water-reducing agent and the composite oil-proofing agent and pour it into the concrete mixing pot and stir for 30-60 seconds to obtain highly oil-resistant concrete.
[0037] By adopting the above steps, the mechanical properties and oil permeation resistance of the obtained high oil permeation resistance concrete can be further improved.
[0038] Beneficial effects of the present invention:
[0039] 1. The present invention adds a composite oil-resistant agent to the raw materials, and the anti-oil seepage effect of the obtained concrete is mainly reflected in the following two aspects: on the physical level, nano-SiO2 can compact the concrete structure by filling particles, thereby blocking the oil seepage path and improving the oil-resistant performance; polyvinyl alcohol polymer blocks the oil seepage path by polymerizing to form a film to cover the pores, thereby improving the anti-oil seepage performance; on the chemical level, FeCl3 reacts with Ca(OH)2 in the concrete to generate Fe(OH)3 nanoparticles, and the Fe(OH)3 nanoparticles block the pores and block the oil seepage path, thereby improving the anti-oil seepage performance; nano-SiO2 reacts with Ca(OH)2 to generate fibrous CSH, and the fibrous CSH blocks the pores, blocks the oil seepage path, and improves the anti-oil seepage performance.
[0040] 2. By adjusting the ratio of silicate cement, fly ash, oil repellent, mixing water, polycarboxylic acid high-performance water reducing agent, coarse aggregate and machine-made sand, the mechanical properties and oil-proof performance of concrete can be improved simultaneously. The anti-seepage grade of the present invention can reach 9-12, and the oil permeability can reach 0.8-1.5%, which meets the needs of nuclear power projects. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the present invention more clear, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and a preferred implementation manner.
[0042] The materials used in the following examples are all commercially available.
[0043] Example 1
[0044] A highly oil-resistant concrete for use in nuclear power projects, comprising the following raw materials by weight:
[0045] PO 42.5 grade ordinary Portland cement 2400g, F class primary fly ash 1170g, composite oil repellent 300g, mixing water 1590g, polycarboxylic acid high performance water reducer 45.5g, coarse aggregate 10480g, machine-made sand 8060g.
[0046] The specific surface area of silicate cement is 344m 2 / kg, density is 3.13kg / m 3 The initial setting time is 270min and the final setting time is 334min.
[0047] The water demand ratio of fly ash is 92%, the activity index is 75%, and the loss on ignition is 1.36%.
[0048] The components of the oil-proofing agent include 59% polyvinyl alcohol, 10% nano-SiO2, 30% FeCl3 and 1% water by weight. The preparation method of the composite oil-proofing agent is the prior art, that is, polyvinyl alcohol, nano-SiO2, FeCl3 and water are mixed and stirred evenly.
[0049] The chloride ion content of the mixing water is 50 mg / L, the alkali content is 1500 mg / L, and the pH value is 5.
[0050] The solid content of polycarboxylic acid high performance water reducing agent is 20.46% and the water reduction rate is 32%.
[0051] The apparent density of coarse aggregate is 2700kg / m 3 , the crushing value is 8% and the mud content is 0.2%.
[0052] The apparent density of machine-made sand is 2640kg / m 3, fineness modulus is 2.8, and mud content is 0.2%.
[0053] The preparation method of the above-mentioned high oil-proof concrete is as follows:
[0054] (1) Pour the coarse aggregate and machine-made sand into the concrete mixing pot and stir for 30 seconds to mix the coarse aggregate and machine-made sand evenly.
[0055] (2) Pour PO 42.5 grade ordinary Portland cement and Class F grade one fly ash into a concrete mixing pot and stir for 30 seconds to ensure that the cement, fly ash, coarse aggregate and machine-made sand are evenly mixed.
[0056] (3) Mix 50% of the mixing water and the polycarboxylic acid high-performance water reducer evenly, then pour into the concrete mixing pot and stir for 30 seconds to mix the cement, fly ash, coarse aggregate, machine-made sand, water reducer and part of the water evenly.
[0057] (4) Mix 25% of the mixing water and 402C oil repellent agent evenly, then pour into the concrete mixing pot and stir for 30 seconds to make the cement, fly ash, coarse aggregate, machine-made sand, water reducer, oil repellent and part of the water evenly mixed.
[0058] (5) Use the remaining 25% of the mixing water to clean the container wall containing the polycarboxylic acid high-performance water reducer and 402C oil repellent and pour it into a concrete mixing pot and stir for 30 seconds to obtain a high oil-resistant concrete material.
[0059] Example 2
[0060] A highly oil-resistant concrete for use in nuclear power projects, comprising the following raw materials by weight:
[0061] The concrete material is composed of the following raw materials by weight: 2450g of PO 42.5 grade ordinary Portland cement, 1130g of Class F first-grade fly ash, 400g of composite oil-proof agent, 1620g of mixing water, 44.5g of polycarboxylic acid high-performance water-reducing agent, 10430g of coarse aggregate, and 7970g of machine-made sand.
[0062] The specific surface area of silicate cement is 330m 2 / kg, density is 3.05kg / m 3 The initial setting time is 260min and the final setting time is 324min.
[0063] The water demand ratio of fly ash is 91%, the activity index is 77%, and the loss on ignition is 1.46%.
[0064] The components of the composite oil-proofing agent include 50% polyvinyl alcohol, 12% nano-SiO2, 37% FeCl3 and 1% water by weight. The preparation method of the composite oil-proofing agent is the same as that of Example 1.
[0065] The chloride ion content of the mixing water is 48 mg / L, the alkali content is 1480 mg / L, and the pH value is 5.2.
[0066] The solid content of polycarboxylic acid high performance water reducing agent is 20.96% and the water reduction rate is 33%.
[0067] The apparent density of coarse aggregate is 2750kg / m 3 , the crushing value is 7.6% and the mud content is 0.18%.
[0068] The apparent density of machine-made sand is 2660kg / m 3 , fineness modulus is 2.7, and mud content is 0.19%.
[0069] The preparation method of the above-mentioned high oil-proof concrete is as follows:
[0070] (1) Pour the coarse aggregate and machine-made sand into the concrete mixing pot and stir for 45 seconds to mix the coarse aggregate and machine-made sand evenly.
[0071] (2) Pour PO 42.5 grade ordinary Portland cement and Class F grade one fly ash into a concrete mixing pot and stir for 45 seconds to mix the cement, fly ash, coarse aggregate and machine-made sand evenly.
[0072] (3) Mix 50% of the mixing water and the polycarboxylic acid high-performance water reducer evenly, then pour it into the concrete mixing pot and stir for 45 seconds to mix the cement, fly ash, coarse aggregate, machine-made sand, water reducer and part of the water evenly.
[0073] (4) Mix 25% of the mixing water and 402C oil repellent agent evenly, then pour into the concrete mixing pot and stir for 45 seconds to make the cement, fly ash, coarse aggregate, machine-made sand, water reducer, oil repellent and part of the water evenly mixed.
[0074] (5) Use the remaining 25% of the mixing water to clean the container wall containing the polycarboxylic acid high-performance water-reducing agent and the 402C oil-proofing agent, and pour it into a concrete mixing pot and stir for 45 seconds to obtain a high oil-proof concrete material.
[0075] Example 3
[0076] A highly oil-resistant concrete for use in nuclear power projects, comprising the following raw materials by weight:
[0077] The concrete material is composed of the following raw materials by weight: 2550g of PO 42.5 grade ordinary Portland cement, 1275g of Class F first-grade fly ash, 459g of composite oil-proof agent, 1785g of mixing water, 51g of polycarboxylic acid high-performance water-reducing agent, 11475g of coarse aggregate, and 7950g of machine-made sand.
[0078] The specific surface area of silicate cement is 325m2 / kg, density is 3.0kg / m 3 The initial setting time is 255min and the final setting time is 320min.
[0079] The water demand ratio of fly ash is 90%, the activity index is 80%, and the loss on ignition is 1.26%.
[0080] The components of the composite oil-proofing agent include 48% polyvinyl alcohol, 15% nano-SiO2, 36% FeCl3 and 1% water by weight. The preparation method of the composite oil-proofing agent is the same as that of Example 1.
[0081] The chloride ion content of the mixing water is 49 mg / L, the alkali content is 1490 mg / L, and the pH value is 5.1.
[0082] The solid content of polycarboxylic acid high performance water reducing agent is 21.0% and the water reducing rate is 34%.
[0083] The apparent density of coarse aggregate is 2760kg / m 3 , the crushing value is 7.8% and the mud content is 0.19%.
[0084] The apparent density of machine-made sand is 2670kg / m 3 , fineness modulus is 2.9, and mud content is 0.18%.
[0085] The preparation method of the above-mentioned high oil-proof concrete is as follows:
[0086] (1) Pour the coarse aggregate and machine-made sand into the concrete mixing pot and stir for 45 seconds to mix the coarse aggregate and machine-made sand evenly.
[0087] (2) Pour PO 42.5 grade ordinary Portland cement and Class F grade one fly ash into a concrete mixing pot and stir for 45 seconds to mix the cement, fly ash, coarse aggregate and machine-made sand evenly.
[0088] (3) Mix 50% of the mixing water and the polycarboxylic acid high-performance water reducer evenly, then pour it into the concrete mixing pot and stir for 45 seconds to mix the cement, fly ash, coarse aggregate, machine-made sand, water reducer and part of the water evenly.
[0089] (4) Mix 25% of the mixing water and 402C oil repellent agent evenly, then pour into the concrete mixing pot and stir for 45 seconds to make the cement, fly ash, coarse aggregate, machine-made sand, water reducer, oil repellent and part of the water evenly mixed.
[0090] (5) Use the remaining 25% of the mixing water to clean the container wall containing the polycarboxylic acid high-performance water-reducing agent and the 402C oil-proofing agent, and pour it into a concrete mixing pot and stir for 45 seconds to obtain a high oil-proof concrete material.
[0091] Example 4
[0092] A highly oil-resistant concrete for use in nuclear power projects, comprising the following raw materials by weight:
[0093] The concrete material is composed of the following raw materials by weight: 2600g of PO 42.5 grade ordinary Portland cement, 1050g of Class F first-grade fly ash, 600g of composite oil-proof agent, 1680g of mixing water, 42.5g of polycarboxylic acid high-performance water-reducing agent, 10330g of coarse aggregate, and 7740g of machine-made sand.
[0094] The specific surface area of PO 42.5 grade ordinary Portland cement is 325m 2 / kg, density is 3.0kg / m 3 The initial setting time is 255min and the final setting time is 320min.
[0095] The water requirement ratio of Class F primary fly ash is 90%, the activity index is 80%, and the loss on ignition is 1.26%.
[0096] The components of the composite oil-proofing agent include 48% polyvinyl alcohol, 15% nano-SiO2, 36% FeCl3 and 1% water by weight. The preparation method of the composite oil-proofing agent is the same as that of Example 1.
[0097] The chloride ion content of the mixing water is 49 mg / L, the alkali content is 1490 mg / L, and the pH value is 5.1.
[0098] The solid content of polycarboxylic acid high performance water reducing agent is 21.0% and the water reducing rate is 34%.
[0099] The apparent density of coarse aggregate is 2760kg / m 3 , the crushing value is 7.8% and the mud content is 0.19%.
[0100] The apparent density of machine-made sand is 2670kg / m 3 , fineness modulus is 2.9, and mud content is 0.18%.
[0101] The preparation method of the above-mentioned high oil-proof concrete is as follows:
[0102] (1) Pour the coarse aggregate and machine-made sand into the concrete mixing pot and stir for 40 seconds to mix the coarse aggregate and machine-made sand evenly.
[0103] (2) Pour PO 42.5 grade ordinary Portland cement and Class F grade one fly ash into a concrete mixing pot and stir for 40 seconds to evenly mix the cement, fly ash, coarse aggregate and machine-made sand.
[0104] (3) Mix 50% of the mixing water and the polycarboxylic acid high-performance water reducer evenly, then pour into the concrete mixing pot and stir for 40 seconds to mix the cement, fly ash, coarse aggregate, machine-made sand, water reducer and part of the water evenly.
[0105] (4) Mix 25% of the mixing water and 402C oil repellent agent evenly, then pour into the concrete mixing pot and stir for 40 seconds to make the cement, fly ash, coarse aggregate, machine-made sand, water reducer, oil repellent and part of the water evenly mixed.
[0106] (5) Use the remaining 25% of the mixing water to clean the container wall containing the polycarboxylic acid high-performance water reducer and 402C oil repellent and pour it into a concrete mixing pot and stir for 40 seconds to obtain a high oil-resistant concrete material.
[0107] Example 5
[0108] A highly oil-resistant concrete for use in nuclear power projects, comprising the following raw materials by weight:
[0109] The concrete material is composed of the following raw materials by weight: 2650g of PO 42.5 grade ordinary Portland cement, 1010g of Class F first-grade fly ash, 700g of composite oil-proof agent, 1710g of mixing water, 41.5g of polycarboxylic acid high-performance water-reducing agent, 10280g of coarse aggregate, and 7650g of machine-made sand.
[0110] The specific surface area of PO 42.5 grade ordinary Portland cement is 325m 2 / kg, density is 3.0kg / m 3 The initial setting time is 255min and the final setting time is 320min.
[0111] The water requirement ratio of Class F primary fly ash is 90%, the activity index is 80%, and the loss on ignition is 1.26%.
[0112] The components of the composite oil-proofing agent include 48% polyvinyl alcohol, 15% nano-SiO2, 36% FeCl3 and 1% water by weight. The preparation method of the composite oil-proofing agent is the same as that of Example 1.
[0113] The chloride ion content of the mixing water is 49 mg / L, the alkali content is 1490 mg / L, and the pH value is 5.1.
[0114] The solid content of polycarboxylic acid high performance water reducing agent is 21.0% and the water reducing rate is 34%.
[0115] The apparent density of coarse aggregate is 2760kg / m 3 , the crushing value is 7.8% and the mud content is 0.19%.
[0116] The apparent density of machine-made sand is 2670kg / m3 , fineness modulus is 2.9, and mud content is 0.18%.
[0117] The preparation method of the above-mentioned high oil-proof concrete is as follows:
[0118] (1) Pour the coarse aggregate and machine-made sand into the concrete mixing pot and stir for 40 seconds to mix the coarse aggregate and machine-made sand evenly.
[0119] (2) Pour PO 42.5 grade ordinary Portland cement and Class F grade one fly ash into a concrete mixing pot and stir for 60 seconds to make the cement, fly ash, coarse aggregate and machine-made sand evenly mixed.
[0120] (3) Mix 50% of the mixing water and the polycarboxylic acid high-performance water reducer evenly, then pour into the concrete mixing pot and stir for 60 seconds to evenly mix the cement, fly ash, coarse aggregate, machine-made sand, water reducer and part of the water.
[0121] (4) Mix 25% of the mixing water and 402C oil repellent agent evenly, then pour into the concrete mixing pot and stir for 60 seconds to make the cement, fly ash, coarse aggregate, machine-made sand, water reducer, oil repellent and part of the water evenly mixed.
[0122] (5) Use the remaining 25% of the mixing water to clean the container wall containing the polycarboxylic acid high-performance water reducer and 402C oil repellent and pour it into a concrete mixing pot and stir for 60 seconds to obtain a high oil-resistant concrete material.
[0123] Comparative Example 1
[0124] Only the composite oil-proofing agent in Example 1 was replaced by the Sino-German Xinya Building Materials 402C oil-proofing agent, and the other raw materials and methods remained unchanged to prepare oil-proof concrete.
[0125] Comparative Example 2
[0126] Only the composite oil-proofing agent in Example 2 was replaced by the Sino-German Xinya Building Materials 402C oil-proofing agent, and the other raw materials and methods remained unchanged to prepare oil-proof concrete.
[0127] Comparative Example 3
[0128] Only the composite oil-proofing agent in Example 3 was replaced by the Sino-German Xinya Building Materials 402C oil-proofing agent, and the other raw materials and methods remained unchanged to prepare oil-proof concrete.
[0129] Comparative Example 4
[0130] Only the composite oil-proofing agent in Example 4 was replaced by the Sino-German Xinya Building Materials 402C oil-proofing agent, and the other raw materials and methods remained unchanged to prepare oil-proof concrete.
[0131] Comparative Example 5
[0132] Only the composite oil-proofing agent in Example 5 was replaced by the Sino-German Xinya Building Materials 402C oil-proofing agent, and the other raw materials and methods remained unchanged to prepare oil-proof concrete.
[0133] The performance of the oil-resistant concrete prepared in Examples 1-5 and Comparative Examples 1-85 was tested by the following method. The results are shown in Table 1.
[0134] The slump is tested according to the Standard for Test Methods of Performance of Ordinary Concrete Mixtures GB / T 50080-2016.
[0135] The compressive strength is tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" GB / T 50081-2019.
[0136] The impermeability grade is tested according to the "Standard for Test Methods for Long-term Performance and Durability of Concrete" GB / T 50082-2024.
[0137] The test method for oil penetration is as follows:
[0138] (1) After the concrete specimens were cured for 28 days, they were placed in an oven at 105°C for 48 hours and weighed after natural cooling.
[0139] (2) Place the weighed test block in a container of engine oil and soak it for 360 days. After soaking, wipe the engine oil on the surface of the test block with a dry towel and weigh it.
[0140] (3) Based on the two weighing results, the oil permeability of the concrete specimen is calculated.
[0141] Table 1. Properties of oil-resistant concrete materials
[0142] Group No. Slump / cm Compressive strength / MPa Impermeability grade Oil penetration rate / % Example 1 200 35 9 1.5 Example 2 192 35.2 11 1.2 Example 3 180 39.7 12 0.8 Example 4 175 42.1 11 1.1 Example 5 170 41.5 10 1.4 Comparative Example 1 195 36 4 2.8 Comparative Example 2 186 35 5 2.6 Comparative Example 3 170 36.1 6 2.5 Comparative Example 4 165 39.2 4 2.8 Comparative Example 5 162 40.1 4 3.0
[0143] From Table 1 we can see that:
[0144] Comparing the product performance of Example 3 with that of Comparative Example 1, it is found that by adding 2% of 402C oil repellent, the compressive strength of the concrete material is increased by 10.3%, the anti-seepage grade is increased by 8 levels, and the oil permeability is reduced by 250%.
[0145] Comparing the product performance in Example 3 with that in Comparative Example 2, it is found that by adding 2% of 402C oil repellent, the compressive strength of the concrete material is increased by 13.4%, the anti-seepage grade is increased by 7 levels, and the oil permeability is reduced by 225%.
[0146] Comparing the product performance in Example 3 with that in Comparative Example 3, it is found that by adding 2% of 402C oil repellent, the slump and compressive strength of the concrete material are increased by 5.8% and 10% respectively, the anti-seepage grade is increased by 6 levels, and the oil permeability is reduced by 212%.
[0147] Comparing the product performance in Example 3 with that in Comparative Example 4, it is found that by adding 2% of 402C oil repellent, the slump and compressive strength of the concrete material are increased by 9% and 1.3% respectively, the anti-seepage grade is increased by 8 levels, and the oil permeability is reduced by 250%.
[0148] Comparing the product performance in Example 3 with that in Comparative Example 5, it is known that by adding 2% of 402C oil-proofing agent, the slump of the concrete material is increased by 11.1%, the anti-seepage grade is increased by 8 grades, and the oil permeability is reduced by 275%.
[0149] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications are also within the protection scope of the present invention.
Claims
1. A highly oil-resistant concrete for use in nuclear power projects, characterized in that: Composed of the following raw materials by weight: Portland cement 9-11%; Fly ash 3.3-5.5%; Oil repellent 1.25-2.5%; Mixing water 6-8%; Polycarboxylic acid high performance water reducing agent 0.18~0.22%; Coarse aggregate 40~50%; Artificial sand 30-35%.
2. The high oil-permeability resistant concrete used in nuclear power engineering according to claim 1, characterized in that: Composed of the following raw materials by weight: Ordinary Portland cement 10-10.6%; Fly ash 4.3-5%; Oil repellent 1.8-2%; Mixing water 6.2-7%; Polycarboxylic acid high performance water reducing agent 0.19~0.2%; Coarse aggregate 41~45%; Artificial sand 31~33%.
3. The high oil-permeability resistant concrete used in nuclear power engineering according to claim 1, characterized in that: The specific surface area of the ordinary Portland cement is 300-400m 2 / kg, density is 2.91-3.13kg / m 3 .
4. The oil-proof concrete for use in nuclear power projects according to claim 1, characterized in that: The water requirement ratio in the fly ash is 90-100%.
5. The highly oil-resistant concrete for use in nuclear power engineering according to claim 1, characterized in that: The oil-proofing agent comprises polyvinyl alcohol, nano-SiO2, FeCl3 and water, and the mass ratio of polyvinyl alcohol, nano-SiO2, FeCl3 and water is (48-59):(10-15):(30-37):
1.
6. The highly oil-resistant concrete for use in nuclear power engineering according to claim 1, characterized in that: The chloride ion content of the mixing water is ≤250 mg / L, the alkali content is ≤1500 mg / L, and the pH value is ≥5.
7. The highly oil-resistant concrete for use in nuclear power engineering according to claim 1, characterized in that: The polycarboxylic acid high-performance water-reducing agent has a solid content of 18-22% and a water-reducing rate of 25-35%.
8. The high oil-permeability resistant concrete used in nuclear power engineering according to claim 1, characterized in that: The apparent density of the coarse aggregate is ≥2700kg / m 3 , crushing value ≤8%, mud content ≤0.2%.
9. The highly oil-resistant concrete for use in nuclear power engineering according to claim 1, characterized in that: The apparent density of the machine-made sand is ≥2600kg / m 3 , mud content ≤0.2%.
10. A method for preparing highly oil-resistant concrete for use in nuclear power projects according to any one of claims 1 to 9, characterized in that: The following steps are connected in sequence: (1) Prepare the raw materials according to the ratio, and divide the mixed water into three parts, which are used in steps (4-6) respectively; (2) Pour the coarse aggregate and machine-made sand into the concrete mixing pot and stir for 30-60 seconds; (3) Pour silicate cement and fly ash into the concrete mixing pot in sequence and stir for 30-60 seconds; (4) Mix part of the mixing water and the polycarboxylic acid high-performance water reducer evenly, then pour into the concrete mixing pot and stir for 30-60 seconds; (5) Mix part of the mixing water and the oil repellent agent evenly and pour into the concrete mixing pot and stir for 30-60 seconds; (6) Use the remaining mixing water to clean the container containing the polycarboxylic acid high-performance water-reducing agent and the composite oil-proofing agent and pour it into the concrete mixing pot and stir for 30-60 seconds to obtain highly oil-resistant concrete.
Citation Information
Patent Citations
Cement additive
CN105565697A
Construction method of oil seepage preventing concrete for oil stain collecting tank
CN110776293A
Oil-proof concrete and preparation method thereof
CN112430059A
Nano SiO2 high-strength waterproof impermeable mortar and preparation method thereof
CN112661461A